Circumscribed choroidal hemangioma: clinical course and treatment - A.F. Brovkina; A.S. Stoyukhina; I.V. Musatkina (РМЖ "Клиническая офтальмология")
A.F. Brovkina1, A.S. Stoyukhina2, I.V. Musatkina3 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2Scientific Research Institute of Eye Diseases, Moscow, Russian Federation 3Moscow City Ophthalmological Center of S.P. Botkin City Clinical Hospital, Moscow, Russian Federation Background: choroidal hemangioma can present as either diffuse or circumscribed. Diffuse choroidal hemangioma has no well-defined borders being localized in the posterior part of the choroid and extending into the pre-equatorial zone. Circumscribed choroidal hemangioma has well-defined borders and have much in common with melanocytic and metastatic tumors. Aim: to determine management strategy of circumscribed choroidal hemangioma (CCH). Patients and Methods: 76 patients with CCH were examined. Clinical presentations and OCT findings and their changes over time were assessed in 41 patients aged 31–83 years (mean age 51.0±2.22 years). CCH sizes were as follows: prominence 0.8–4.0 mm (on average, 2.27±0.13 mm), diameter 2.64–14.0 mm (on average, 7.49±0.42 mm). Retrospective study of the outcomes of prior brachytherapy in 35 patients (median age 36.34 years) was performed. Before brachytherapy, median prominence of CCH was 3.47 mm and maxi mum diameter 10.6 mm. Results: CCH was diagnosed accidentally in a half of the patients (51.2%). The tumors were predominantly localized in the macula and paramacular area (48 eyes), less common in juxtapapillary area (16 eyes), and the nasal half of the fundus (12 eyes). Complete resorption of subretinal fluid and tumor was reported in 18 eyes. In one eye (tumor prominence 4.25 mm, retinal detachment, and low vision for 8 years), the outcome of brachytherapy was poor. Radiation maculopathy has developed in 8 patients (22.86%) with CCH near the macula. Conclusion: CCH is a torpid benign choroidal tumor with good vision at baseline which requires dynamic follow-up and OCT to monitor retina, retinal detachment height, and tumor thickness. Progressive loss of vision and progressive retinal detachment are considered indications for treatment. Asymptomatic or non-progressive CCHs require careful dynamic follow-up only. Keywords: choroid, circumscribed choroidal hemangioma, op tical coherence tomography, brachytherapy, clinical signs. For citation: Brovkina A.F., Stoyukhina A.S., Musatkina I.V. Circumscribed choroidal hemangioma: clinical course and treatment. Russian Journal of Clinical Ophthalmology. 2020;20(2):56–62. DOI: 10.32364/2311-7729-2020-20-2-56-62.